2014
DOI: 10.1097/ncc.0b013e3182980255
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Cancer and Its Treatment on Physical Activity Levels and Behavior in Hong Kong Chinese Childhood Cancer Survivors

Abstract: It is essential for nurses to correct misconceptions about physical activity among childhood cancer survivors and their parents and, most importantly, to advocate the principle of regular physical activity for these children, with the aim of enhancing their physical and psychological well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 33 publications
3
56
0
Order By: Relevance
“…19 Another study found that less physically active childhood cancer survivors felt more fatigued and had less physical strength and endurance. 18 The lack of observed association among PA, motor performance, and physical function in our study could be a result of several factors. First, the current study identified only one child with motor performance impairment.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…19 Another study found that less physically active childhood cancer survivors felt more fatigued and had less physical strength and endurance. 18 The lack of observed association among PA, motor performance, and physical function in our study could be a result of several factors. First, the current study identified only one child with motor performance impairment.…”
Section: Discussionmentioning
confidence: 64%
“…Anthracycline treatment has well-documented, potentially long-term cardiotoxic side effects, and it potentially limits physical function. 16,17 Few studies have investigated whether motor performance or physical function impairments are related to PA levels in children who have completed treatment for ALL, 5,6,18,19 and to date, these studies have included childhood cancer survivors with a wide range in age and time since completing treatment. Given how important it is that children participate in PA for their normal growth and development, and recognizing that a suitable time to reintroduce habitual PA is once treatment for ALL is completed, 20 a better understanding of the factors associated with higher or lower PA levels in children shortly after completing treatment for ALL is needed.…”
mentioning
confidence: 99%
“…13 Florin et al 13 found that 52.8% of the survivors of childhood cancer in the United States did not meet the level of regular physical activity proposed by the Centers for Disease Control and Prevention. Chung et al 14 found similarly low levels of physical activity among childhood cancer survivors in Hong Kong: 35.8% did not perform regular physical exercise, and only 18% were thinking of starting to exercise regularly within the next 6 months. The key issues preventing them from engaging in regular physical exercise were cancer-related fatigue and decreased muscle strength and endurance.…”
mentioning
confidence: 81%
“…64 Similarly, in a study of Korean children and adolescents aged 9-16 years who had completed treatment for cancer at least 6 months previously, Chung et al found that physical activity decreased from pre-diagnosis to survivorship, and 92.2% of survivors did not meet recommended physical activity levels. 65 Finally, in a Swiss study of young adult and adult survivors of childhood cancer, Rueegg et al found that only 52% of survivors met physical activity guidelines after a mean of 19.5 years post-diagnosis. 66 AYAs are a population with unique motivations and barriers to exercise adherence that must be taken into consideration when promoting a physically active lifestyle.…”
Section: Barriers To Exercise and Intervention Preferences Of Childhomentioning
confidence: 98%
“…68 In a study of adolescent survivors of childhood cancer, Chung et al found that fatigue, decreased strength and endurance following treatment, and concern about academic performance prevented survivors from participating in regular physical activity. 65 Gilliam et al found that higher levels of family and peer support, greater family income, male sex, and higher self-efficacy were associated with higher levels of physical activity among childhood cancer survivors aged 8-16 years. 69 In a group of adolescent cancer survivors, Wright et al found that lack of time was the biggest barrier to exercise, while social support motivated survivors to participate in physical activity.…”
Section: Barriers To Exercise and Intervention Preferences Of Childhomentioning
confidence: 98%